Ethical hacking workshop : explore a practical approach to learning and applying ethical hacking techniques for effective cybersecurity /: explore a practical approach to learning and applying ethical hacking techniques for effective cybersecurity. (2023) - Pillay, Rishalin; Abutheraa, Mohammed
No abstract available